2016
DOI: 10.3171/2015.10.jns151959
|View full text |Cite
|
Sign up to set email alerts
|

Association of nosocomial infections with delayed cerebral ischemia in aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVE Delayed cerebral ischemia (DCI) is a recognized complication of aneurysmal subarachnoid hemorrhage (aSAH) that contributes to poor outcome. This study seeks to determine the effect of nosocomial infection on the incidence of DCI and patient outcome. METHODS An exploratory analysis was performed on 156 patients with aSAH enrolled in the Cerebral Aneurysm Renin Angiotensin System study. Clinical and radiographic data were analyzed with univariate analysis to detect risk factors for the development of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…However, the exact interplay between these factors has yet to be elucidated, and a rather complex interaction between dynamic systems seems more likely than a simple linear causation [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact interplay between these factors has yet to be elucidated, and a rather complex interaction between dynamic systems seems more likely than a simple linear causation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, EVDAI is considered to be one of the most important nosocomial infections that negatively influence the neurological outcome of aSAH patients. Acknowledged mechanisms behind this clinical observation are the exacerbation of inflammatory processes, thrombogenicity, and disturbances of CSF-dynamics [8][9][10][11][12][13][14]. According to the literature, between 8% and 63% of aSAH patients eventually undergo a permanent CSF diversion (shunting) procedure [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with acute SAH possess increased risk of nosocomial infections secondary to a multitude of risk factors, for example, altered level of consciousness interfering with the ability to clear secretions, compromised host defenses, and presence of catheters and tubes, as well as decreased mobility while bed-ridden. 7 Serum sodium disorder is a well-characterized complication of SAH via the disrupted hypothalamic-pituitary axis, manifesting as syndrome of inappropriate secretion of antidiuretic hormone, salt wasting syndrome, or diabetes insipidus. 23,28 Cardiopulmonary dysfunction emerges not only as specific complications after SAH, including Takotsubo cardiomyopathy and neurogenic pulmonary edema, 15 but may also ensue if vasospasm prevention and treatment resulted in overhydration.…”
Section: Discussionmentioning
confidence: 99%
“…Infections included clinical and microbiological confirmation of meningitis, pneumonia, bacteremia, colitis, wound infection, and urinary tract infection at any point during hospitalization, treated with antimicrobials. 7 Serum sodium was measured every 2-3 days, and hyponatremia and hypernatremia with serum sodium concentrations less than 135 mmol/L and more than 150 mmol/L, respectively, were defined as serum sodium disorders. 23 Cardiopulmonary complications included clinically significant congestive heart failure, Takotsubo cardiomyopathy, 15 and pulmonary edema, which were diagnosed based on the results of chest radiographs, electrocardiograms, and echocardiograms and were treated with diuretics, inotropes, or steroids, as directed by a cardiologist.…”
Section: Patient Selection Study Design and Clinical Evaluationmentioning
confidence: 99%
“…In their most recent study Foreman et al found that nosocomial infection is independently associated with delayed cerebral ischemia. They suggested that this association is hypothesized to be partly causative through the exacerbation of systemic inflammation leading to thrombosis and subsequent ischemia (16) .…”
Section: A B C Dmentioning
confidence: 99%